A practical guide to using econometrics - Studenmund, A. H.; Johnson, Bruce K. (Harlow, England Pearson, 2017)
The Seventh Edition is appropriate for all levels: beginner econometric readers, regression users seeking a refresher, and experienced practitioners who want a convenient reference. Praised as one of the most important texts in the last 30 years, the book retains its clarity and practicality in previous editions with a number of substantial improvements throughout.
The Seventh Edition is appropriate for all levels: beginner econometric readers, regression users seeking a refresher, and experienced practitioners who want a convenient reference. Praised as one of the most important texts in the last 30 years, the book retains its clarity and practicality in previous editions with a number of substantial improvements throughout.--Provided by publisher.
An Overview of Regression Analysis -- Ordinary Least Squares Learning to Use Regression Analysis -- The Classical Model -- Hypothesis Testing and Statistical Inference -- Specification: Choosing the Independent Variables -- Specification: Choosing a Functional Form -- Multicollinearity -- Serial Correlation -- Heteroskedasticity -- Running Your Own Regression Project -- Time-Series Models -- Dummy Dependent Variable Techniques -- Simultaneous Equations -- Forecasting Experimental and Panel Data.
Global edition.
Authorized adaptation from the United States same edition, entitled Using econometrics : a practical guide.
Includes bibliographical references and index.
Keywords: Econometrics; Regression analysis